PENGARUH RELIGIUSITAS, PENGETAHUAN AKUNTANSI SYARIAH, PELATIHAN PROFESIONAL DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA AKUNTANSI BERKARIR DI LEMBAGA KEUANGAN SYARIAH - Fadel Baha; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to provide an analysis of the influence of religiosity, Islamic accounting knowledge, professional training and market considerations on the interest of career accounting students in Islamic financial institutions. This study uses primary data by distributing questionnaires. The population used is S1 Accounting FEB UNISMA students who have taken Islamic accounting courses. The sampling technique used purposive sampling method with predetermined criteria for respondents. Testing the hypothesis in this study using the simultaneous test (jji F), the coefficient of determination ((), and partial test (t test). The results of this study interpret that simultaneously the variables of religiosity, sharia accounting knowledge, professional training and market considerations have a significant effect on the interest of accounting students for careers in Islamic financial institutions, while partially religiosity, sharia accounting knowledge, professional training and time market considerations have no significant effect. positive towards the interest of accounting students for a career in Islamic financial institutions. Keywords: Religiosity, Knowledge of Islamic Accounting, Professional Training and Market Considerations, and Interest of Career Students in Islamic Financial Institutions.